Analyzing the Implementation of Educational Accounting at Madrasah Tsanawiyah Tarbiyah Islamiyah, Koto Lubuk Jambi Village - Jipa, Ester Salsanabila; Nada Salsabila,; Ratih Kusumastuti, (Jurnal Mutiara Ilmu Akuntansi, 2023)
This research aimed to assess the alignment of the accounting practices at Madrasah Tsanawiyah Tarbiyah Islamiyah in Koto Lubuk Village, Jambi, with the generally accepted accounting principles. The data for this study were gathered from both primary and secondary sources, utilizing techniques such as interviews and documentation. The findings revealed that Madrasah X in Jambi City employed accounting procedures that included daily cash books, ledgers, income statements, balance sheets, and a list of fixed assets. However, the institution did not record depreciation for fixed assets at the end of the period and failed to prepare financial statements as per SFAS ETAP, which includes activity reports, financial position statements, cash flow statements, and notes to the financial statements. In conclusion, the application of accounting practices in X Jambi City, was found not to align with the generally accepted accounting principles.